Multifunction Shoe Cabinet for Small Living Space - Wang, Ming Ler; Sidek, Ahmad Anwar Safwan (Research in Management of Technology and Business, 2023)
Urbanization and rapid growth of population in cities has affected the demand of more low-cost housing apartments but it leads to issue of less living space for the residents. To decrease the limited space be taken out by furniture, multifunction furniture has become the smart solution to counter the issue. The adaption of multifunctional element in necessary furniture has to be taken more into account. Shoe cabinet as one of the most important furniture in a household is not excluded from it. The objectives of this research are to identify the design criteria of the multifunction shoe cabinet, to design, and to develop a prototype of the multifunction shoe cabinet for small living space. This research uses quantitative approach such as questionnaire to collect data and information. The questionnaire was distributed to 60 respondents that live in apartments in Johor Bahru of Johor via Google Form online. The findings of the survey questionnaire have shown the design criteria respondents preferred on the multifunction shoe cabinet, which are wood as main material, designed with extra shoe storage, seating, and mirror, minimalist style, wood colour, built with tilt-out drawers, and short-height shoe cabinet. The process of creating the design started with ideations, continued with idea developments, design survey, final design, and technical drawings. The process then continued with building a mock-up of the design, creating the bill of material (BOM), and finally fabrication of the designed prototype. Every phase of the process contributes improvement and add details to the design of the multifunction shoe cabinet in order to meet the required design criteria. A real size multifunction shoe cabinet prototype has successfully manufactured according to the sketched final design at the end of this research. In conclusion, the purpose idea of multifunction shoe cabinet can help to solve space efficient problem, while provide storage function and other extra function at the same time. These design criteria were implemented into the design of the multifunction shoe cabinet. The findings and information provided in this research can be used as reference for relating research in the future and for improvement of shoe cabinets’ design.